Biochemistry. Section 2. Molecular biology. Biochemistry of intercellular communications, tissues and physiological functions : tests for students of the second year study speciality 222 "Medicine" - Ivanchenko, D. H.; Krisanova, N. V.; Rudko, N. P.; Іванченко, Дмитро Григорович; Крісанова, Наталія Вікторівна; Рудько, Наталія Петрівна (Запорізький державний медико-фармацевтичний університет, 2023)
This manual is recommended to use for students of II International faculty (the second year of study) for independent work in Biochemistry discipline at home and in class.